Is the Distribution of Income Compatible with a Stable Distribution? - John K. Dagsvik; Bjørn H. Vatne (Statistics Norway, Research Department, 1999)
Mandelbrot (1961) proposed to apply the class of Pareto-Levy distributions - which belong to the Stable distributions - as a framework for modelling income distributions. He also presented theoretic arguments in favor of the Pareto-Levy distributions. In this paper we provide additional theoretical justification for this class of distributions. We also use micro data on individual market income to estimate the parameters of a Pareto-Levy distribution. Several estimation methods have been applied. The estimated Pareto-Levy distribution appears to fit the data well.
Keywords: C13; D31; 330; Stable distributions; Pareto-Levy distributions; Income distributions